Gender decision-making the case of the Department of Agrarian Reform Region VI and Iloilo Province Officers - Alvior, Rosalie B.; Oredina, Ma. Sonia Grace (1995.)
This study was undertaken to determine whether there is gender difference in the attitude/behavior of decision makers among the top level of management of the Department of Agrarian Reform Region VI and Iloilo Province Offices. A total of fifteen (15) respondents or eighty percent of the total top level decision makers in the Department of Agrarian Reform Region Vi and Iloilo Province Offices took part in the study. They were given questionnaires, which were divided into two sections: the respondent's profile and the decision maker's characteristics. The study focused on identifying the gender differences in relation to their attitude as a decision maker. By doing so we could understand better the DAR top level decision maker's and harness their potentials to enable them to be active players in CARP implementation. The result of the study showed that there were certain attitudes or behaviors that differentiate both male and female decision makers.
Research paper (BA 200 - Business Research) -- Iloilo City : University of the Philippines in the Visayas-College of Management, April 1, 1995.